Metaphysics and Laws of Nature in Early Modern Philosophy : An Introduction - Manzo, Silvia (2021)
The term "metaphysics" is quite difficult to define as it refers to a broad branch of philosophy that was diversely understood from a variety of philosophical perspectives throughout its long history. Despite criticisms and attacks received from several fronts, it is still a major area of contemporary philosophy. It investigates the nature of reality in its most possible general way or "being" considered in general. The legendary story goes that the term was coined in the first century by Andronicus of Rhodes. As editor of Aristotle's works, he called a group of fourteen books tá metá tá phusiká, which means literally "the ones after the physical ones," from which came the shorter word "metaphysics" (metaphusiká). While "physics" is the name of a treatise and a discipline that according to Aristotle studies nature and change, the etymology of "metaphysics" allowed for several interpretations of the name depending on the sense in which the Greek prefix metáis understood. If it is...